Method for producing an antibacterial fixed denture

By using nano-antibacterial powder generated during the denture fabrication process, the problem of uneven distribution of antibacterial agents is solved, achieving stability of antibacterial effect and cost reduction, making it suitable for antibacterial fixed dentures in the field of dental materials.

CN120392557BActive Publication Date: 2025-11-18QINGDAO HUAXINHUA DENTAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510604780.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-11-18
Estimated Expiration
2045-05-12

AI Technical Summary

Technical Problem

The antibacterial agents in existing antibacterial dentures are unevenly distributed, resulting in unstable antibacterial effects and high costs.

Method used

The method for preparing nano-antibacterial powder involves reacting zinc salt and cerium salt in an organic solvent to generate a zinc-cerium solid solution, adding orthosilicate and surfactant to form silicon-coated nanoparticles, spraying them onto the surface of the denture blank and curing them to form a uniform antibacterial structure.

Benefits of technology

The antibacterial properties of dentures are improved. The uniform distribution and synergistic catalytic effect of nanoparticles enhance the antibacterial effect, reduce production costs, and facilitate industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120392557B_ABST
    Figure CN120392557B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of oral cavity materials, and particularly relates to a preparation method of an antibacterial fixed denture, which comprises the following steps: (1) adding an alkaline precipitant solution into a mixed solution of zinc salt and cerium salt to perform strong stirring, so as to obtain a mixed reactant; (2) adding orthosilicate into the mixed reactant, then adding deionized water to perform stirring, so as to obtain a zinc-cerium solid solution precipitate; the zinc-cerium solid solution precipitate is separated, dispersed, washed and dried to obtain a nano antibacterial powder; (3) dispersing the nano antibacterial powder into an organic solvent first, then adding the nano antibacterial powder into an enamel solution to obtain a nano antibacterial enamel solution; then the nano antibacterial enamel solution is sprayed onto the surface of a fixed denture blank, and then solidification is performed to obtain an antibacterial fixed denture. The nano antibacterial powder is prepared more simply, the production cost is lower, and the use method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oral materials technology, specifically relating to a method for preparing an antibacterial fixed denture. Background Technology

[0002] Currently, with the improvement of people's living standards and the deepening of population aging, the demand for dental materials is increasing, among which the antibacterial properties of dentures have become an important aspect. Therefore, developing a denture with excellent antibacterial function is particularly important.

[0003] Chinese Patent CN118637907A discloses an antibacterial zirconia-based denture and its preparation method. The preparation method provided by this invention includes: mixing a portion of zirconia, a portion of yttrium oxide, and a portion of a colorant to obtain a first mixture; mixing the remaining zirconia, inorganic antibacterial agent, remaining yttrium oxide, and remaining colorant to obtain a second mixture; sequentially pouring the first mixture and the second mixture into a mold for dry pressing to obtain an antibacterial composition ceramic block precursor with a multi-layer structure; sequentially subjecting the antibacterial composition ceramic block precursor to cold isostatic pressing, pre-sintering, and final firing treatments to obtain the antibacterial zirconia-based denture; the second mixture is located at the gingival position of the antibacterial zirconia-based denture; by mass, the antibacterial zirconia-based denture includes the following raw materials: 80-95 parts of zirconia, 1-5 parts of inorganic antibacterial agent, 1-5 parts of yttrium oxide, and 1-5 parts of colorant.

[0004] The aforementioned patent has a multi-layered structure, resulting in uneven distribution of the antibacterial agent in the denture and unstable antibacterial effect. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing antibacterial fixed dentures. The antibacterial fixed dentures obtained during the preparation process can provide more active oxygen due to the abundant hydroxyl groups on their surface, thereby improving the antibacterial performance and antibacterial rate of the fixed dentures, and the cost is low.

[0006] The technical solution adopted by this invention to solve its technical problem is:

[0007] The method for preparing the antibacterial fixed denture according to the present invention includes the following steps:

[0008] (1) Dissolve zinc salt and cerium salt in an organic solvent, dissolve alkaline precipitant in the same organic solvent, and heat them separately to obtain a zinc salt and cerium salt mixed solution and an alkaline precipitant solution. Then add the alkaline precipitant solution to the zinc salt and cerium salt mixed solution to carry out the precipitation reaction to obtain a mixed reactant solution.

[0009] (2) Add orthosilicate to the mixed reactant solution, then add deionized water to carry out the coating reaction to obtain silicon-coated zinc-cerium solid solution precipitate. Separate the silicon-coated zinc-cerium solid solution precipitate, then disperse the silicon-coated zinc-cerium solid solution precipitate in an organic solvent, add surfactant to continue dispersion, and then dry the silicon-coated zinc-cerium solid solution precipitate to obtain nano antibacterial powder.

[0010] (3) Add nano antibacterial powder to the glaze to obtain nano antibacterial glaze, then spray the nano antibacterial glaze onto the surface of the fixed denture blank, and then cure to obtain antibacterial fixed denture.

[0011] In step (1), the zinc salt is one of zinc chloride, zinc sulfate, zinc acetate or zinc nitrate, the cerium salt is one of cerium ammonium nitrate, cerium nitrate, cerium sulfate or cerium chloride, the alkaline precipitant is one of sodium hydroxide, potassium hydroxide or ammonia water, the concentration of zinc salt in organic solvent is 0.2-1 mol / L, the concentration of cerium salt in organic solvent is 0.005-0.03 mol / L, the concentration of alkaline precipitant in organic solvent is 1.5-2.5 mol / L, and the ratio of the amount of zinc salt and cerium salt to the amount of alkaline precipitant is 1:1.5-2.5.

[0012] In step (1), the organic solvent is an alcohol, which is one or more of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol or butanol.

[0013] In step (1), the heating temperature is 30-80℃, the precipitation reaction temperature is 30-80℃, and the precipitation reaction time is 5-20min.

[0014] In step (2), the orthosilicate is ethyl orthosilicate or methyl orthosilicate, and the molar ratio of orthosilicate to zinc salt is 1:20-50.

[0015] In step (2), the molar ratio of deionized water to zinc salt is 3-8:1, and the coating reaction time is 30-60 min.

[0016] In step (2), the organic solvent is an alcohol, which is one or more of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol or butanol.

[0017] In step (2), the surfactant is one or more of silane coupling agents or titanate coupling agents, and the mass ratio of surfactant to zinc salt is 0.05-0.2:1.

[0018] In step (2), the nano antibacterial powder is a nano cube with an arc-shaped edge and a particle size of 5-30 nm.

[0019] In step (3), the nano antibacterial powder is dispersed in the glaze in a monodisperse form. The mass ratio of the nano antibacterial powder to the glaze is 0.04-0.1:1. The curing temperature is 750-930℃ and the curing time is 2-4h.

[0020] The glaze formula is as follows: calcium feldspar, kaolin, quartz and hydroxyapatite are made into a base material in a ratio of 1:1:1:1, and then the flux silica, colorant and solvent are added. The mass ratio of silica to base material is 0.1-1%, preferably 0.5%.

[0021] The nano-antibacterial powder of this invention is mainly composed of silicon-coated zinc-cerium solid solution. Zinc salt, cerium salt, and an alkaline precipitant react to form a zinc-cerium solid solution. After hydrolysis with orthosilicate, silica forms on the surface of the zinc-cerium solid solution. The addition of a surfactant, i.e., a coupling agent, promotes better dispersion of the silicon-coated zinc-cerium solid solution particles in the organic solvent. Furthermore, the introduction of the coupling agent activates the silica on the surface of the nano-antibacterial powder. Therefore, the nano-antibacterial powder prepared by the precipitation of the silicon-coated zinc-cerium solid solution can be fully mixed with the glaze through intermolecular interactions between the surface silica and the silica in the glaze, ensuring the stable existence of the nano-antibacterial powder in the glaze. The glaze is then sprayed onto the surface of the fixed denture blank. The material used to fix the denture blank has undergone surface roughening treatment. In ceramics with a metal oxide matrix, such as zirconium dioxide, the silica in the glaze attracts zirconium dioxide in the raw body under the action of a coupling agent. The glaze penetrates into the pores on the surface of the raw body, resulting in a denture with uniform material. During the heat treatment and curing process of the denture, silica can form a stable and solid surface. Hydrogen bonds can be formed between the molecular chains of hydroxyapatite, silica, zirconium dioxide, and coupling agent, resulting in a stable structure. After high-temperature curing, hydroxyapatite and silica have a dense and uniform structure. The silica-coated zinc-cerium solid solution, coupling agent, silica in the glaze, hydroxyapatite, and zirconium dioxide in the raw body form a complete antibacterial system. Finally, the nano-antibacterial powder is dispersed and fixed on the surface of the fixed denture, thereby improving the antibacterial performance of the fixed denture.

[0022] The beneficial effects of this invention are:

[0023] Nanoparticle antibacterial powder is simpler to prepare and has lower production costs. It can be directly added to glaze liquid, which facilitates subsequent curing and molding, and is easy to industrialize.

[0024] Orthosilicates hydrolyze into silica in water, forming a coating on the surface of zinc-cerium solid solution particles, anchoring the zinc-cerium onto the silica. Due to the mutual attraction between silica particles, the nano-antibacterial powder dissolves more stably in the glaze. The addition of cerium provides more active oxygen, enhancing the catalytic activity of the zinc-cerium solid solution. The resulting antibacterial fixed denture enhances the structural stability of the uniformly attached zinc-cerium solid solution on the denture surface. Furthermore, the uniformly distributed zinc-cerium solid solution on the denture surface can catalyze the generation of oxidative free radicals from oxygen and water in the mouth, interacting with enzymes and proteins within bacterial cells, disrupting cell structure, and thus inhibiting bacterial growth and reproduction.

[0025] In addition, zinc-cerium synergistic catalysis is also a feature of this invention. Zinc-cerium synergistic catalysis utilizes the synergistic effect between zinc and cerium to improve catalytic activity and efficiency. By doping cerium, the catalytic activity of zinc is improved. Experiments have shown that neither zinc alone nor cerium alone can achieve the purpose of this invention. Attached Figure Description

[0026] Figure 1 This is a SEM image of the nano-antibacterial powder prepared according to the present invention. Detailed Implementation

[0027] The present invention will be further described below with reference to embodiments.

[0028] Example 1

[0029] (1) Dissolve 860g zinc acetate and 20g cerium ammonium nitrate in 8000ml methanol, and dissolve 390g potassium hydroxide in 4000ml methanol. Heat the solutions to 40℃ to obtain a zinc salt and cerium salt mixed solution and a potassium hydroxide methanol solution. Then add the potassium hydroxide methanol solution to the zinc salt and cerium salt mixed solution and stir at 40℃ for 10min to carry out a precipitation reaction to obtain a mixed reactant.

[0030] (2) Dissolve 22g of tetraethyl orthosilicate in 1100ml of methanol, then add it to the mixed reactants. Add 440ml of deionized water and stir for 40min to obtain a zinc-cerium solid solution precipitate. Centrifuge the zinc-cerium solid solution precipitate at room temperature, then disperse it in 1000ml of ethanol. Add 47g of silane coupling agent KH570 and stir for 30min to continue dispersion. Add deionized water and stir for 20min, then centrifuge. Disperse the precipitate again in ethanol and wash with deionized water. Dry by rotary evaporation to obtain nano-antibacterial powder. Use ethanol as the dispersion medium to detect the particle size of the nano-antibacterial powder. The average particle size is 15nm. The nano-antibacterial powder is a cube with arc-shaped edges, dispersed in the glaze in a monodisperse form, such as... Figure 1 As shown;

[0031] (3) Add 3.6g of nano antibacterial powder to 90g of glaze and stir to dissolve to obtain nano antibacterial glaze. Then spray the nano antibacterial glaze onto the surface of the denture blank and heat it at 750℃ for 4h to cure it to obtain antibacterial fixed denture.

[0032] Example 2

[0033] (1) Dissolve 534g of zinc chloride and 10g of cerium nitrate in 8000ml of ethanol, and dissolve 279g of sodium hydroxide in 4000ml of ethanol. Heat the solutions to 30°C to obtain a zinc salt and cerium salt mixed solution and a potassium hydroxide ethanol solution. Then add the sodium hydroxide methanol solution to the zinc salt and cerium salt mixed solution and stir at 30°C for 20min to carry out a precipitation reaction to obtain a mixed reactant.

[0034] (2) Dissolve 16g of methyl orthosilicate in 900ml of ethanol, then add it to the mixed reactants, then add 560ml of deionized water and stir for 40min to obtain zinc-cerium solid solution precipitate. Centrifuge the zinc-cerium solid solution precipitate at room temperature, then disperse the zinc-cerium solid solution precipitate in 1000ml of ethanol, add 47g of silane coupling agent KH570 and stir for 30min to continue dispersion, then add deionized water and stir for 20min, centrifuge, then disperse again in ethanol and wash with deionized water, then dry by rotary evaporation to obtain nano antibacterial powder with an average particle size of 20nm;

[0035] (3) Add 6g of nano antibacterial powder to 100g of glaze and stir to dissolve to obtain nano antibacterial glaze. Then spray the nano antibacterial glaze onto the surface of the denture blank and heat it at 800℃ for 3h to cure it to obtain antibacterial fixed denture.

[0036] Example 3

[0037] (1) Dissolve 430g zinc sulfate and 20g cerium chloride in 8000ml ethylene glycol, and dissolve 240g ammonia in 4000ml ethylene glycol. Heat the solutions to 50℃ to obtain a zinc salt and cerium salt mixed solution and a potassium hydroxide ethylene glycol solution. Then add potassium hydroxide methanol solution to the zinc salt and cerium salt mixed solution and stir at 50℃ for 15min to carry out a precipitation reaction to obtain a mixed reactant.

[0038] (2) Dissolve 16.8g of tetraethyl orthosilicate in 1100ml of ethylene glycol, then add it to the mixed reactants, and then add 380ml of deionized water and stir for 40min to obtain zinc-cerium solid solution precipitate. Centrifuge the zinc-cerium solid solution precipitate at room temperature, then disperse the zinc-cerium solid solution precipitate in 1000ml of ethanol, add 87g of silane coupling agent KH570 and stir for 30min to continue dispersion, then add deionized water and stir for 30min, centrifuge, then disperse again in ethanol and wash with deionized water, and dry by rotary evaporation to obtain nano antibacterial powder with an average particle size of 10nm;

[0039] (3) Add 9g of nano antibacterial powder to 90g of glaze and stir to dissolve to obtain nano antibacterial glaze. Then spray the nano antibacterial glaze onto the surface of the denture blank and heat it at 910℃ for 3h to cure it to obtain antibacterial fixed denture.

[0040] Example 4

[0041] (1) Dissolve 880g of zinc chloride and 50g of cerium chloride in 8000ml of propanol, and dissolve 400g of sodium hydroxide in 4000ml of propanol. Heat the solutions to 60℃ respectively to obtain a zinc salt and cerium salt mixed solution and a potassium hydroxide propanol solution. Then add the potassium hydroxide propanol solution to the zinc salt and cerium salt mixed solution and stir at 60℃ for 15min to carry out a precipitation reaction to obtain a mixed reactant.

[0042] (2) Dissolve 67g of tetraethyl orthosilicate in 1100ml of propanol, then add it to the mixed reactants, and then add 380ml of deionized water and stir for 50min to obtain zinc-cerium solid solution precipitate. Centrifuge the zinc-cerium solid solution precipitate at room temperature, then disperse the zinc-cerium solid solution precipitate in 1000ml of ethanol, add 87g of silane coupling agent KH570 and stir for 45min to continue dispersion, then add deionized water and stir for 30min, centrifuge, then disperse again in ethanol and wash with deionized water, and dry by rotary evaporation to obtain nano antibacterial powder with an average particle size of 5nm;

[0043] (3) Add 10g of nano antibacterial powder to 120g of glaze and stir to dissolve to obtain nano antibacterial glaze. Then spray the nano antibacterial glaze onto the surface of the denture blank and heat it at 930℃ for 2 hours to cure it, thus obtaining antibacterial fixed denture.

[0044] Example 5

[0045] (1) Dissolve 480g zinc sulfate and 10g cerium nitrate in 8000ml propylene glycol, and dissolve 240g sodium hydroxide in 4000ml propylene glycol. Heat them to 80℃ respectively to obtain a zinc salt and cerium salt mixed solution and a potassium hydroxide propylene glycol solution. Then add the potassium hydroxide propylene glycol solution to the zinc salt and cerium salt mixed solution and stir at 80℃ for 5min to carry out the precipitation reaction and obtain the mixed reactants.

[0046] (2) Dissolve 18.5g of tetraethyl orthosilicate in 1100ml of propylene glycol, then add it to the mixed reactants, and then add 400ml of deionized water and stir for 60min to obtain zinc-cerium solid solution precipitate. Centrifuge the zinc-cerium solid solution precipitate at room temperature, then disperse the zinc-cerium solid solution precipitate in 1000ml of ethanol, add 66g of silane coupling agent KH570 and stir for 30min to continue dispersion, then add deionized water and stir for 25min, centrifuge, then disperse again in ethanol and wash with deionized water, and dry by rotary evaporation to obtain nano antibacterial powder with an average particle size of 30nm;

[0047] (3) Add 9g of nano antibacterial powder to 100g of glaze and stir to dissolve to obtain nano antibacterial glaze. Then spray the nano antibacterial glaze onto the surface of the denture blank and heat it at 850℃ for 2 hours to cure it, thus obtaining antibacterial fixed denture.

[0048] Example 6

[0049] (1) Dissolve 560g zinc nitrate and 100g cerium sulfate in 8000ml butanol, and dissolve 260g sodium hydroxide in 4000ml butanol. Heat them to 30℃ respectively to obtain a zinc salt and cerium salt mixed solution and a potassium hydroxide butanol solution. Then add the potassium hydroxide butanol solution to the zinc salt and cerium salt mixed solution and stir at 30℃ for 20min to carry out the precipitation reaction and obtain the mixed reactants.

[0050] (2) Dissolve 18.5g of methyl orthosilicate in 1100ml of butanol, then add it to the mixed reactants, and then add 420ml of deionized water and stir for 60min to obtain zinc-cerium solid solution precipitate. Centrifuge the zinc-cerium solid solution precipitate at room temperature, then disperse the zinc-cerium solid solution precipitate in 1000ml of ethanol, add 73g of silane coupling agent KH570 and stir for 40min to continue dispersion, then add deionized water and stir for 35min, centrifuge, then disperse again in ethanol and wash with deionized water, and dry by rotary evaporation to obtain nano antibacterial powder with an average particle size of 25nm;

[0051] (3) Add 13.5g of nano antibacterial powder to 150g of glaze and stir to dissolve to obtain nano antibacterial glaze. Then spray the nano antibacterial glaze onto the surface of the denture blank and heat it at 900℃ for 2 hours to cure it, thus obtaining antibacterial fixed denture.

[0052] The glaze formulations in Examples 1-6 are as follows: calcium feldspar, kaolin, quartz, and hydroxyapatite are mixed in a ratio of 1:1:1:1 to form a base material, and then the flux silica, colorant, and ethanol are added. The mass ratio of silica to the base material is 0.5%.

[0053] Comparative Example 1

[0054] Steps (1) and (2) are omitted. In step (3), no nano antibacterial powder is added to the glaze. The remaining steps are the same as in Example 1.

[0055] Comparative Example 2

[0056] In step (3), 0.36g of nano antibacterial powder is converted into 0.36g of pure zinc oxide, and the remaining steps are the same as in Example 1.

[0057] Comparative Example 3

[0058] No silane coupling agent was added in step (2), and the remaining steps were the same as in Example 1.

[0059] Comparative Example 4

[0060] In step (1), only zinc acetate is used, and the amount of zinc acetate is the same as the total amount of zinc acetate and cerium ammonium nitrate in Example 1. The remaining steps are the same as in Example 1.

[0061] The short-term antibacterial data of Examples 1-6 and Comparative Examples 1-4 were tested according to the film-sealing method in QB / T2591-2003 "Test Method for Antibacterial Properties and Antibacterial Effects of Antibacterial Plastics". The long-term antibacterial data were obtained by placing antibacterial fixed dentures in a simulated oral environment for 6 months, and then testing them according to the film-sealing method in QB / T2591-2003 "Test Method for Antibacterial Properties and Antibacterial Effects of Antibacterial Plastics". The test results are shown in Table 1 below.

[0062]

[0063] As shown in the table above, compared with Example 1, the antibacterial fixed denture prepared using the present invention has a significantly better antibacterial effect than the denture without antibacterial materials in Comparative Example 1; compared with Example 1, the antibacterial fixed denture prepared using the present invention has a better antibacterial effect than the denture prepared using commercially available ordinary zinc oxide in Comparative Example 2; compared with Example 1, the absence of silane coupling agent in Comparative Example 3 during preparation results in poor dispersion of nanoparticles, thus weakening the antibacterial effect; compared with Example 1, the absence of cerium ammonium nitrate in Comparative Example 4 during preparation prevents the formation of a zinc-cerium solid solution, reducing catalytic activity and efficiency. Using zinc alone cannot achieve the purpose of the present invention, and using cerium alone has weak antibacterial ability, also failing to achieve the purpose of the present invention. The antibacterial fixed denture has an antibacterial rate of over 96% against Escherichia coli and over 94% against Staphylococcus aureus.

Claims

1. A method for preparing an antibacterial fixed denture, characterized in that, Includes the following steps: (1) Dissolve zinc salt and cerium salt in an organic solvent, dissolve alkaline precipitant in the same organic solvent, and heat them separately to obtain a zinc salt and cerium salt mixed solution and an alkaline precipitant solution. Then add the alkaline precipitant solution to the zinc salt and cerium salt mixed solution to carry out the precipitation reaction to obtain a mixed reactant solution. The zinc salt is one of zinc chloride, zinc sulfate, zinc acetate or zinc nitrate; the cerium salt is one of cerium ammonium nitrate, cerium nitrate, cerium sulfate or cerium chloride; the alkaline precipitant is one of sodium hydroxide, potassium hydroxide or ammonia water; and the organic solvent is an alcohol, which is one or more of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol or butanol. (2) Add orthosilicate to the mixed reactant solution, then add deionized water to carry out the coating reaction to obtain silicon-coated zinc-cerium solid solution precipitate. Separate the silicon-coated zinc-cerium solid solution precipitate, then disperse the silicon-coated zinc-cerium solid solution precipitate in an organic solvent, and add a surfactant to continue the dispersion. Then dry the silicon-coated zinc-cerium solid solution precipitate to obtain nano antibacterial powder; the orthosilicate is tetraethyl orthosilicate or methyl orthosilicate, the surfactant is one or more of silane coupling agents, the organic solvent is an alcohol organic compound, the alcohol organic compound is one or more of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol or butanol, and the nano antibacterial powder is a nano cube with an arc-shaped edge and a particle size of 5-30 nm; (3) Add nano antibacterial powder to the glaze to obtain nano antibacterial glaze, then spray the nano antibacterial glaze onto the surface of the fixed denture blank, and then cure to obtain antibacterial fixed denture.

2. The method for preparing antibacterial fixed dentures according to claim 1, characterized in that, In step (1), the concentration of zinc salt in the organic solvent is 0.2-1 mol / L, the concentration of cerium salt in the organic solvent is 0.005-0.03 mol / L, the concentration of alkaline precipitant in the organic solvent is 1.5-2.5 mol / L, and the ratio of the amount of zinc salt and cerium salt to the amount of alkaline precipitant is 1:1.5-2.

5.

3. The method for preparing antibacterial fixed dentures according to claim 1, characterized in that, In step (1), the heating temperature is 30-80℃, the precipitation reaction temperature is 30-80℃, and the precipitation reaction time is 5-20min.

4. The method for preparing antibacterial fixed dentures according to claim 1, characterized in that, In step (2), the molar ratio of orthosilicate to zinc salt is 1:20-50.

5. The method for preparing antibacterial fixed dentures according to claim 1, characterized in that, In step (2), the molar ratio of deionized water to zinc salt is 3-8:1, and the coating reaction time is 30-60 min.

6. The method for preparing antibacterial fixed dentures according to claim 1, characterized in that, In step (2), the mass ratio of surfactant to zinc salt is 0.05-0.2:

1.

7. The method for preparing antibacterial fixed dentures according to claim 1, characterized in that, In step (3), the nano antibacterial powder is dispersed into the glaze in a monodisperse form. The mass ratio of the nano antibacterial powder to the glaze is 0.04-0.1:

1. The curing temperature is 750-930℃ and the curing time is 2-4h.

Citation Information

Patent Citations

  • Antibacterial zirconia-based false tooth and preparation method thereof

    CN118637907A

  • Method for preparing sepiolite-loaded chitosan-zinc antibacterial powder

    CN108991014A

  • Method for preparing inorganic nano-germicide powder

    CN1784975A